Ulos dan Refigurasi Makna Keselamatan dalam Konteks Batak Kristen - Novalina, Martina (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2025)
This article examines ulos as a symbol of hope and salvation in Batak culture and how this symbol can be refigured in the light of the Gospel through Paul Ricoeur’s symbolic hermeneutics and Stephen Bevans’ contextual theology. The study explores the dynamic relationship between cultural symbols and divine revelation as a dialogical expression of faith and culture. Employing a qualitative–theological approach, it applies symbolic analysis to Batak cultural texts (rituals, narratives, and socio-spiritual meanings of ulos) and to relevant biblical passages, particularly John 1:14 and Revelation 21:3-5. The findings reveal that ulos mediates theological understanding of love, sacrifice, and hope, which are fundamentally consonant with the Gospel message of universal salvation in Christ. From a hermeneutic perspective, ulos functions as an incarnational sign of divine love that envelops humanity. Within a contextual–theological framework, it serves as a local vessel of divine revelation, connecting Christian faith to Batak cultural identity. This study concludes that the reinterpretation of local symbols, such as the ulos, is not merely cultural but deeply theological, an integral dimension of the Church’s effort to inculturate the Christian faith in Indonesia, thereby affirming the sacredness of local wisdom, meaning, and spiritual expression within the framework of the Gospel. Abstrak Artikel ini mengkaji ulos sebagai simbol harapan dan keselamatan dalam kebudayaan Batak serta bagaimana simbol tersebut dapat direfigurasi dalam terang Injil melalui pendekatan hermeneutika simbolik Paul Ricoeur dan teologi kontekstual Stephen Bevans. Penelitian ini menelusuri relasi dinamis antara simbol budaya dan wahyu ilahi sebagai bentuk dialog antara iman dan kebudayaan lokal. Metode yang digunakan adalah kualitatif-teologis dengan analisis simbolik terhadap teks budaya Batak (ritual, narasi, dan makna sosial-spiritual ulos) dan teks-teks biblika yang relevan (terutama Yoh. 1:14 dan Why. 21:3-5). Hasil penelitian menunjukkan bahwa ulos memediasi pemahaman teologis mengenai kasih, pengorbanan, dan pengharapan, yang secara hakiki sejalan dengan pesan Injil tentang keselamatan universal di dalam Kristus. Dalam perspektif hermeneutika simbolik, ulos dapat dipahami sebagai tanda inkarnasional kasih Allah yang menyelimuti manusia, sementara dalam kerangka teologi kontekstual, ia berfungsi sebagai wadah lokal bagi pewahyuan ilahi yang menghubungkan iman Kristen dengan identitas budaya Batak. Artikel ini menegaskan bahwa reinterpretasi simbol lokal seperti ulos tidak sekadar bersifat kultural, melainkan teologis, menjadi bagian integral dari upaya inkulturasi iman Kristen di Indonesia yang menghargai nilai, makna, dan ekspresi religius masyarakat setempat.